E-Learning in Europe - Results and Recommendations : Thematic Monitoring under the LEONARDO DA VINCI-Programme - Attwell, Graham [Verfasser]; Dirckinck-Holmfeld, Lone [Verfasser]; Fabian, Peter [Verfasser]; Karpati, Andrea [Verfasser]; Littig, Peter [Verfasser]; Fahle, Klaus [Verfasser] (My University, 2005)
"The goal of the study is to analyse relevant eLearning projects which are being conducted through the Leonardo da Vinci programme, and to indicate how and to what extent these projects address issues and challenges in the thematic area of eLearning. The analysis of these projects is to help to define which themes are not sufficiently covered by current projects and to provide recommendations for follow-up activities as part of the thematic monitoring and for future Leonardo projects concerning eLearning. In total, the thematic monitoring examined 149 projects from throughout Europe and the information gathering and research was undertaken by a project team of five subject experts from Denmark, Hungary, Slovakia, Great-Britain and Germany." (BIBB)
Keywords: L 4.2.3 Internetbasiertes Lernen / E-Learning; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.2 Europa; E-Learning; EU-Programm; LEONARDO; Europa